Small distances:: between richard long and aboriginal australians (Palíndromo, 2021)
In order to discuss the approximation among international contemporary art and artworks from non-Western cultures we approached the exhibition Magiciens de La Terre, held at the Centre Pompidou and at the Grande Halle de La Villet, both in Paris, between May 18, 1989 and August14, 1989. The scope of this approach were the piece A Circle of Red Earth, by Richard Long, 1989, and the painting Yam Dreaming, by artist of Yuendumu community, 1989, Alice Spring, Australia. Considering that, in the 1980s, a theory of post-coloniality emerged and the anthropological studies on the relations that Aboriginal Australian Communities held towards their visual objects, a question emerged. The question was concerning the way the theory of post-coloniality influences the organization of the exhibition in order to reflect on the debate about how to deal with visual objects made by non-Western artists and their local histories.
Keywords: Contemporary art .; Exhibition Magiciens de la Terre .; non-Western art; Aboriginal Australian art; Richard Long.